Triumphing Over Injustice: A Daughter’s Account of Leadership During the Violent Birth of Bangladesh - Ahmad, Sharmin (Juniata Voices, 2024)
Distinguished Malloy Lecture, February 16, 2023. Sharmin Ahmad is the daughter of Tajuddin Ahmad. He was a political activist that fought for freedom, democracy, and liberty. Due to his continual determination, he served as the first prime minister of Bangladesh. As his daughter, she witnessed a genocide against her people and other violent crimes in the War of Liberation. In this lecture, Ahmad explores stories of heroism and sacrifice, courage and compassion. She also identifies points of leadership and how her father, against all odds, made victory possible.